Clinical evaluation of personalized Helicobacter pylori treatment guided by PCR detection from fecal samples: a real-world study - Peng, Ruolin; Zhang, Zhimei; Yang, Chuchu; Xu, Zhengyuan; Wang, Jiabin; Chen, Lei; Gao, Sujun; Tao, Jian; Xi, Meijuan; Ye, Xiaofeng; Shen, Lu; Zhan, Qiang; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundGrowing antibiotic resistance in Helicobacter pylori (H. pylori) diminishes eradication therapy effectiveness, emphasizing the need for accurate, non-invasive diagnostic techniques. This study aims to assess the clinical utility of PCR analysis of fecal samples for detecting antibiotic resistance in guiding personalized treatment for H. pylori infection.MethodsA retrospective, observational study was conducted across 13 hospitals within Jiangsu Province. Fecal samples were analyzed using fluorescence PCR for the 23S rRNA and gyrA genes, indicating clarithromycin and levofloxacin resistance. Then, individualized eradication recommendations were proposed for the H. pylori-positive patients. A follow-up was performed one year later to evaluate the eradication outcomes in a routine medical environment, with participants having provided informed consent.ResultsA total of 387 participants completed the eradication treatment, with an overall success rate of 91.0% (352/387, 95% CI: 87.6%-93.6%). Among them, 310 individuals received a 14-day course of bismuth quadruple therapy (BQT), achieving an eradication rate of 90.0% (279/310, 95% CI: 86.1%-93.1%). 77 participants were treated with high-dose dual therapy (HDDT) for the same duration, resulting in a slightly higher eradication rate of 94.8% (73/77, 95% CI: 87.2%-98.6%), although this difference was not statistically significant (P=0.188). No significant differences in eradication rates were observed among various BQT antibiotic combinations (P=0.208). The eradication rates for HDDT, based on either vonoprazan or esomeprazole, were 96.8% (61/63, 95% CI: 89.0%-99.6%) and 85.7% (12/14, 95% CI: 57.2%-98.2%), respectively, without a significant difference (P=0.304).ConclusionPCR detection from fecal samples targeting the resistance genes of H. pylori is effective in guiding personalized treatments, highlighting its clinical utility and potential for broader application.